CURRICULUM BUILDING FOR PROSPECTIVE INDUSTRIAL ACCOUNTANTS. - Bowers, Russell (The Accounting Review, 1953)
Abstract The curriculum for prospective industrial accountants might begin from either of two viewpoints. One is that of taking a conventional body of subject matter which is organized into textbooks and inadvertently presenting this material as an end in itself. Almost needless to say this approach takes the more difficult part of curriculum building for granted. Thus, the curriculum builder would only select and prescribe course titles; the instructor would follow up the routine task of presenting the "tried and the true" while keeping student interest alive and enhancing it as much as possible. The aim of each course in such a curriculum is to "give the student a good understanding of" something or other which is rarely well defined. The principal defect of this approach is its poor adaptability to the needs of a changing world. A different approach would place less emphasis on conventional course content as pertains to both subject matter and method of teaching. In the beginning there would be little apparent presumption of a fixed body of subject matter to be covered or learned, but the instructor, of course, would have an abundance of subject matter at hand. This is based partly on the belief that the candidate to a major profession cannot know long in advance much about what the later requirements of his profession will be. The student must discover these objectives as his educational development unfolds, and his opinions will not be held for long. Most of this curriculum would be prescribed with but few elective courses. Instead of subject matter to be taught, the learning process would be the focus of attention.